2014
DOI: 10.4028/www.scientific.net/amr.899.298
|View full text |Cite
|
Sign up to set email alerts
|

Design of Balcony from the Point of View of Daylighting

Abstract: Balconies are horizontal overhanging structures whose main function is a connection between interior and exterior space. Moreover, they increase an area of a room and they also can have a presentable, architectural and aesthetic purpose. There are a lot of requirements on the balconies, for example the requirements on static properties, thermal bridges, railings or fire safety. From the point of view of building physics, we can consider the balcony as the fixed shading construction which can reduce overheating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 1 publication
3
3
0
Order By: Relevance
“…Figure 9a, however, illustrated an interesting cut-off point for design decision-making as balcony depths below 1.0 m had, in the majority of cases, sDA values falling within the preferred threshold whereas balcony depths above 1.0 m would tend to have sDA values falling, on average, within the accepted threshold. As expected from Al-Sallal et al [13], Kim and Kim [11], Gábrova [14], Xue et al [12] and Dahlan et al [15,16], the addition of balconies was determinant in reducing the ASE (Figure 9b). However, this study identified that balconies deeper than 1.5 m will achieve null ASE and therefore are optimum to avoid glare and overheating due to direct solar radiation.…”
Section: -Window Widthsupporting
confidence: 74%
See 4 more Smart Citations
“…Figure 9a, however, illustrated an interesting cut-off point for design decision-making as balcony depths below 1.0 m had, in the majority of cases, sDA values falling within the preferred threshold whereas balcony depths above 1.0 m would tend to have sDA values falling, on average, within the accepted threshold. As expected from Al-Sallal et al [13], Kim and Kim [11], Gábrova [14], Xue et al [12] and Dahlan et al [15,16], the addition of balconies was determinant in reducing the ASE (Figure 9b). However, this study identified that balconies deeper than 1.5 m will achieve null ASE and therefore are optimum to avoid glare and overheating due to direct solar radiation.…”
Section: -Window Widthsupporting
confidence: 74%
“…The mean and median values for both solar orientations were classified as sDA acceptable and ASE tolerable, although the West façade resulted in higher levels of ASE, possibly due to the fact that the number of occupied hours in the afternoons is higher than in the mornings. The use of balconies wider than the windows (ratio of balcony width to window width = 2) decreased the daylight performance (Figure 12a) but also prevented glare (Figure 12b), echoing results found by [11,13,14]Al-Sallal et al [13]. The ratio of balcony width to window width of 1 and 2 showed similar performance for ASE, with most part of the cases classified as null, reinforcing the importance of having balconies with full window width.…”
Section: -Window Widthsupporting
confidence: 62%
See 3 more Smart Citations